SOCIETY IN THE SYSTEM OF "MAN - SOCIETY - NATURE" - Kleshnia, Hanna (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Unlimited faith in human genius and rationality has led to deplorable results as irreversible environmental crises engulfed the entire planet. The practiced theory of the self-organizing and self-regulating power of the market economy, which eliminated the stateregulator from the space of being was the last straw that destroyed the fragile balance of the biogeocenosis. The aim and tasks area philosophical analysis of the role of society in the classical triangle of "man – society – nature" in the context of the biosocial crisis of the globalized world. Research methods are a combination of philosophical and general scientific approaches and methods. The systems approach reflects the self-organization and structuring of systems in the conditions of the synergistic universal quality of the world. An interdisciplinary synergetic methodology is also used to understand the dynamics of self-organization in the system "man – society – nature. Research results. The development of civilization has set a very important task for modern science: resolving the contradiction between the needs of the human community and the limited natural resources. Striving for the fullest possible satisfaction of ever-growing needs in an environmental crisis is a manifestation of irresponsibility. And this state is actively supported by the value preferences of the mass consumer society. Various forms of society and nature interaction and their dynamics are among the main components of human progress, individual events of human history, although they have a noticeable impact in some cases, they are neither directed nor of any duration. In addition, we must take into account the concept of society to a greater extent than the role of the individual in co-evolutionary processes. Discussion. Moiseev N. states that understanding complex systemic interdependencies is the content of the philosophical approach to solving environmental problems. The postmodern society has been sufficiently studied both by foreign (D. Bell, P. Kozlovsky, J.-F. Lyotard, E. Toffler) and domestic researchers (V. Horbatenko, L. Drotianko, S. Ordenov and others). As a result, N. Luhmann noted that against the "foggy" background of globalization, there is no common understanding of the concept of "society" at all. H. Arendt noted that power does not act as legalized violence but is a regulator of joint actions by generally recognized institutional ties, and the atomization of individuals in a mass society is associated with a violation of social ties. Based on her conclusions, we can note that over the past few years, humanity has found itself in conditions of total control and digital instrumentalization as a result of the fight against the COVID-19 pandemic. Conclusion. Representatives of the Club of Rome have repeatedly noted that limiting the consumption of natural resources, developing an environmentally oriented economy is the most important condition for the transition of society to the path of harmonizing the "society-nature" system and stabilizing the environmental situation. Consequently, ensuring the harmonization of the material and spiritual life of society, the ecological and socio-economic aspirations of mankind on the basis of worldview should be combined in the future, and the environmental policy of states in the globalizing world should become dominant because it determines the possibilities and ways of survival of mankind as a part of nature.